(untitled) (Journal of Scientific Research, 2009)
The synthesis of new solid charge-transfer (CT) complexes using 5,6-dimethyl-2,1,3-benzoselnadiazoles as donors with 1,4-naphthaquinone; 1,8-dihydroxyanthraquinone, 2-hydroxy-1,4-naphthaquinone and 2,3-dichloro-4,5-dicyano-p-benzoquinone (DDQ) as acceptor are reported. These complexes are characterized by elemental analysis, IR, UV-V, and 1HNMR spectroscopic data. Solid conductivity for 1, 2 and 3 compounds revel that they are not conductors. The calculated HOMO is largely localized on the selnadiazoles fragment, while the calculated LUMO of the studied molecule is seen to be substantially localized along the C–C axis of the conjugated system. Keywords: Charge transfer complexes; Dimethylbenzoselnadiazoles; Naphthaquinone; Dihydroxyanthraquinone; Hydroxynaphthaquinone; Dichlorodicyanobenzoquinone (DDQ); Semi-empirical (PM3) methods. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2590 J. Sci. Res. 1 (3), 569-575 (2009)